FACTORS INFLUENCING BIOSECURITY ADOPTION ON LAYING HEN FARMERS - Lestari, V.S.; Natsir, A.; Sirajuddin, S.N.; Kasim, K.; Ali, H.M.; Saadah, S.; Mawardi, M. (Diponegoro University, 2012)
The present study was undertaken to identify factors that influences biosecurity adoption on layinghen farmers in Sidrap district, South Sulawesi. This district was choosen because beside it was famousas the center of laying hen farms, it was also as one of districts in South Sulawesi which suffered fromAvian influenza outbreak. Total samples were 60 respondents. The samples were choosen throughstratified random sampling from two subdistricts which had the most populous of layer smallholders,namely Baranti and Maritengngae. Data were obtained through observations and interviews using aquestionnaire. Data were analyzed using a score based on biosecurity status. Biosecurity status wasobtained based on the adoption of biosecurity measures which consisted of 9 stages: farm inputs, trafficonto farms, distance from sources of pathogens to shed, exposure of farm, biosecurity at farm boundary,biosecurity between farm boundary and shed, biosecurity at the shed door, traffic into the shed andsusceptibility of the flock. Multiple regression model was employed to analyze the data. The studyrevealed that the adoption biosecurity were associated with gender, age, education, farming experience,farm-income, family size and social capital. These variables contributed 20% variation in biosecurityadoption of laying hen farms. However, only farm income, family size and social capital were the majorfactors influencing to the adoption of biosecurity (P<0.05).